Civil rights injunction for the protection of fundamental - Brewer-Carias, Allan R. (Ediciones Olejnik, 2023)
This book on The Civil Rights Injunction for the protection of Funda-mental Rights. The Latin American «Amparo» Proceeding, is the original version of the text I wrote for the Couse of Lectures I gave, as Adjunct Professor of Law, on a Seminar on Judicial Protection of Fundamental Rights in Latin America: the Amparo Proceeding, at the Columbia Law School in New York, University of Columbia, during the years 2006-2008. The Seminar was intended to examine the most recent trends in the constitutional and legal regulations in all Latin American countries regarding the “amparo” suit, action or recourse– including the old habeas corpus writ and the new habeas data actions or recourses. By means of a comparative constitutional law approach, also with reference to the United States civil rights injunctions, the Course analyzed this Latin American institution departing from the regulation of the “amparo” guarantee established in Article 25 of the 1969 American Convention of Human Rights which entered into force in 1978 after being ratified by all Latin American States. The amparo suit or proceeding is not only an effective judicial means for the restoration of the injured constitutional rights that has been harmed, similar to the reparative or restorative civil rights injunctions in the United States, but it is also the effective judicial means for the protection of such rights and guaranties when threatened to be violated or harmed. This latter amparo suit is then similar to the preventive civil rights injunctions in the United States; “preventive” in the sense of avoiding harm; which, in this case, “seeks to prohibit some discrete act or series of acts from occurring in the future”, and is designed “to avoid future harm to a party by prohibiting or mandating certain behavior to another party”. From this point of view, thus, in a constitutional comparative law approach, the Latin American amparo action or proceeding, is a judicial remedy similar to the civil rights injunctions (restorative or preventive) in the United States. ALLAN R. BREWER–CARÍAS